Педагогіка духовності - Хмельницький інститут ПрАТ «ВНЗ «МАУП» (My University, 2012)
У Частині 1 збірки подано наукові статті за матеріалами роботи Всеукраїнської науково-практичної конференції "Пересопницьке Євангеліє: духовна святиня українського народу" (до 455-річчя з початку написання Пересопницького Євангелія), яка відбулася 12 травня 2011 року. У Частині 2 збірки подано матеріали Всеукраїнської науково-практичної конференції "Історія, культура та освіта: християнський вимір", яка відбулася 4 травня 2012 року. У наукових публікаціях порушуються актуальні питання: історії створення Пересопницького Євангелія, духовності народу, історичного розвитку України та ін. Part 1 of the collection presents scientific articles based on the materials of the All-Ukrainian Scientific and Practical Conference "Peresopnytsia Gospel: Spiritual Shrine of the Ukrainian People" (to the 455th anniversary of the beginning of the writing of the Peresopnytsia Gospel), which took place on May 12, 2011. Part 2 of the collection presents materials of the All-Ukrainian Scientific and Practical Conference "History, Culture and Education: Christian Dimension", which took place on May 4, 2012. The scientific publications raise topical issues: the history of the creation of the Peresopnytsia Gospel, the spirituality of the people, the historical development of Ukraine, etc.